2019
DOI: 10.1111/jon.12680
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Microembolic Signals in the Cerebral Circulation on Transcranial Doppler after Intravenous Sulfur Hexafluoride Microbubble Infusion

Abstract: BACKGROUND AND PURPOSE Microembolic signals (MES) are detectable by transcranial Doppler monitoring and associated with increased risk of first or recurrent ischemic stroke. MES detection can also illuminate stroke etiology and the effect of prophylactic treatment. MES detection cannot accurately distinguish between stroke‐related microemboli and ultrasound contrast agents. These agents contain microbubbles and are frequently used in neuro‐ and cardiovascular diagnostics. We aimed to assess how long after cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Monitoring with the TCD-X system for 3.5 hours found that sulfur hexafluoride microbubbles (SonoVue, Milan, Italy) persisted for 12-77 minutes (median 40.5 minutes), leading the authors to conclude that MES detection for the identification of stroke-related microemboli should wait at least 77 minutes following the administration of SF6. 117 Further evaluation and validation of the TCD-X is still warranted.…”
Section: Electronic or Mechanical Steeringmentioning
confidence: 99%
“…Monitoring with the TCD-X system for 3.5 hours found that sulfur hexafluoride microbubbles (SonoVue, Milan, Italy) persisted for 12-77 minutes (median 40.5 minutes), leading the authors to conclude that MES detection for the identification of stroke-related microemboli should wait at least 77 minutes following the administration of SF6. 117 Further evaluation and validation of the TCD-X is still warranted.…”
Section: Electronic or Mechanical Steeringmentioning
confidence: 99%
“…Previously, printed microparticles and nanoparticles with cargo mixed into the bulk polymer have been reported by Rolland et al 25 and later by Key et al 26 Independently Tao and Desai, 27 Guan et al, 28 and Abid et al 29 10 μm, which are too large for intravenous administration, as they can potentially block pulmonary and sinusoidal capillaries. 30 Nonetheless, intravenous injection of particles of a few microns in size has been widely reported as clinically relevant and previously applied for microbubble as ultrasound markers, 31 Alzheimer disease treatment, 32 and for in vivo studies of radiolabeled PLA microparticles biodistribution and biodegradation. 33 In this work, we propose a method for the fabrication of printed polymer capsules based on soft lithography, which exploits microwell arrays.…”
Section: ■ Introductionmentioning
confidence: 99%